2014
DOI: 10.1108/oir-01-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

A study of blog networks to determine online social network properties from the tie strength perspective

Abstract: Purpose -Most studies on tie strength have focused on its definition, calculation and applications, but have not paid much attention to how tie strength can help analyse online social networks. Because ties play different roles in a network depending on their strength, the purpose of this paper is to explore the relationship between tie strength and network behaviours. Design/methodology/approach -The authors propose a simple metric for tie strength measurement and then apply it to an online social network ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…It has often been assumed that relationships within a network are equal, but that fails to consider that people maintain relationships with varying tie strength [16]. The role of ties within a network varies depending on the network's strength, and different tie strengths affect the social structure differently [16]. Individuals with strong ties have greater similarities and share more intimate information, so treating all relationships as equal degrades predictive modeling [20].…”
Section: Tie Strength and Information Diffusionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has often been assumed that relationships within a network are equal, but that fails to consider that people maintain relationships with varying tie strength [16]. The role of ties within a network varies depending on the network's strength, and different tie strengths affect the social structure differently [16]. Individuals with strong ties have greater similarities and share more intimate information, so treating all relationships as equal degrades predictive modeling [20].…”
Section: Tie Strength and Information Diffusionmentioning
confidence: 99%
“…For example, Rejeb-Khachlouf et al [8] concluded that dense networks contribute to a faster diffusion of information. Chui et al [16] validated that structural properties of a social network are exhibited in an online network and that tie strength is an influencing factor of certain network behavior.…”
Section: Collaborative Networkmentioning
confidence: 99%
See 3 more Smart Citations